Majalah Mangle: Penjaga Kearifan Lokal dan Peranannya Dalam Melestarikan Bahasa dan Budaya Sunda 1957 -1998 - Hilman Rosmana (Department of History, Faculty of Humanities, Diponegoro University, 2017)
This article analyzes on the development of Mangle as local magazine in the mid of modernization and its role to preserved Sundanese cultural heritage. There are three periods that successfully divided to analyze the development of the magazine, pioneering (1957-1959), triumph (1959-1972), and surviving (1972-1998) periods. By using historical method, it can be revealed conditions and problems faced by the editor of Mangle in each period. In the meantime, there are several factors that led the existence of Mangle for more than half a century. Some of these factors are 1) editorial persistence in maintaining commitment, 2) ability to present information according the reader’s needs and wishes, and 3) reader loyalty. Mangle proved faithfully to be a preservation media for Sundanese culture. Through the editorial teams, Mangle was successfully managed to maintain the author's regeneration by let the new generation of Sundanese writers involved into the magazine pubilcation.